EFFECT OF BOTANICALS FOR MANAGEMENT OF LEAF BLAST AND ENHANCING YIELD TRAITS IN RICE - PANDEY, SANDEEP (Current Botany, 2018)
Field experiments were undertaken during kharif 2012 and 2013 under irrigated ecosystem to evaluate the efficacy of botanicals along with standard fungicides for assessing per cent disease incidence, plant height, number of tiller per plant, number of spikelet per panicle, panicle length, 100-grain weight and grain yield against blast of rice. Pooled data of two years suggest that neem based commercial biopesticides with azadiractin as active ingredients were found effective in reducing disease severity and improving the yield attribute of the crop and proves promising products when compared to standard fungicides. Among the botanicals the spraying of Achook, Neem Azal T/S, Neem gold and Tricure shows significant reduction in disease severity, along with improving yield attributes, increasing the 100-grain weight and grain yield.